Osteopontin is not required for the development of Th1 responses and viral immunity. - Abel, B; Freigang, S; Bachmann, M; Boschert, U; Kopf, M (2005)
Osteopontin (OPN) has been defined as a key cytokine promoting the release of IL-12 and hence inducing the development of protective cell-mediated immunity to viruses and intracellular pathogens. To further characterize the role of OPN in antiviral immunity, OPN-deficient (OPN-/-) mice were analyzed after infection with influenza virus and vaccinia virus. Surprisingly, we found that viral clearance, lung inflammation, and recruitment of effector T cells to the lung were unaffected in OPN-/- mice after influenza infection. Furthermore, effector status of T cells was normal as demonstrated by normal IFN-gamma production and CTL lytic activity. Moreover, activation and Th1 differentiation of naive TCR transgenic CD4+ T cells by dendritic cells and cognate Ag was normal in the absence of OPN in vitro. Contrary to a previous report, we found that OPN-/- mice mounted a normal immune response to Listeria monocytogenes. In conclusion, OPN is dispensable for antiviral immune responses against influenza virus and vaccinia virus.